Antihypertension Activity of Gynura procumbens (L.) Merr. Extract On Blood Pressure And Monoxide Nitrogen Levels In Male White Rats - Rahimatul Uthia; Dina Yuliana; Widya Kardela (JURNAL PROTEKSI KESEHATAN, 2021)
Hypertension is closely related to vasodilation disorders because of the decreased availability of nitrogen monoxide (NO). The purpose of this study was to determine the decrease in blood pressure and nitrogen monoxide (NO) levels in rats after administration of Gynura procumbens leaves extract. The results showed that the administration of Gynura procumbens leaves extracts significantly reduced blood pressure and increased NO levels. From the results of Duncan's test, it was found that the dose of 300mg / Kg BW showed a better effect on increasing NO levels (p <0.05). From the results of the study, it can be concluded that the ethanol extract of Gynura procumbens leaves has an antihypertensive activity that can reduce blood pressure and increase the NO level.